Alginate Nanoparticles for Drug Delivery and Targeting - Severino, Patricia; da Silva, Classius F.; Andrade, Luciana N.; de Lima Oliveira, Daniele; Campos, Joana; Souto, Eliana B. (Current Pharmaceutical Design, 2019)
Nanotechnology refers to the control, manipulation, study and manufacture of structures and devices at the nanometer size range. The small size, customized surface, improved solubility and multi-functionality of nanoparticles will continue to create new biomedical applications, as nanoparticles allow to dominate stability, solubility and bioavailability, as well controlled release of drugs. The type of a nanoparticle, and its related chemical, physical and morphological properties influence its interaction with living cells, as well as determine the route of clearance and possible toxic effects. This field requires cross-disciplinary research and gives opportunities to design and develop multifunctional devices, which allow the diagnosis and treatment of devastating diseases. Over the past few decades, biodegradable polymers have been studied for the fabrication of drug delivery systems. There was extensive development of biodegradable polymeric nanoparticles for drug delivery and tissue engineering, in view of their applications in controlling the release of drugs, stabilizing labile molecules from degradation and site-specific drug targeting. The primary aim is to reduce dosing frequency and prolong the therapeutic outcomes. For this purpose, inert excipients should be selected, being biopolymers, e.g. sodium alginate, commonly used in controlled drug delivery. Nanoparticles composed of alginate (known as anionic polysaccharide widely distributed in the cell walls of brown algae which, when in contact with water, forms a viscous gum) have emerged as one of the most extensively characterized biomaterials used for drug delivery and targeting a set of administration routes. Their advantages include not only the versatile physicochemical properties, which allow chemical modifications for site-specific targeting but also their biocompatibility and biodegradation profiles, as well as mucoadhesiveness. Furthermore, mechanical strength, gelation, and cell affinity can be modulated by combining alginate nanoparticles with other polymers, surface tailoring using specific targeting moieties and by chemical or physical cross-linking. However, for every physicochemical modification in the macromolecule/ nanoparticles, a new toxicological profile may be obtained. In this paper, the different aspects related to the use of alginate nanoparticles for drug delivery and targeting have been revised, as well as how their toxicological profile will determine the therapeutic outcome of the drug delivery system.
Keywords: nanoparticles